Synthesis and Characterization of Hydroxyapatite based on Green Mussel Shells (Perna viridis) with Calcination Temperature Variation Using the Precipitation Method - Yusril, Yusuf (Universiti Malaysia Perlis (UniMAP), 2018)
Link to publisher's homepage at http://ijneam.unimap.edu.my